EVALUASI PENGARUH POLA KERJA TERHADAP FATIQUE UNTUK MENGURANGI JUMLAH KECELAKAAN - Ishardita Pambudi Tama; Oke Oktavianty (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2014)
Fatigue experienced by most of the public transport drivers cause a decrease in the level of vigilance while driving . The demands of the company or demands to be able to make ends meet cause most of the public bus drivers keep working even in conditions of fatigue so that the condition often causes accidents . To determine the level of awareness of the driver while driving is done by spreading the data collection questionnaire and use vigilance test software . Data obtained by using software vigilance test is Average Reaction Time ( ART ) . The data is then analyzed to see regression correlation relation to the number of variables which are , long drive , long breaks and the number of breaks . From the analysis it was concluded that the ART is directly proportional to the length of time driving or driving , but inversely proportional to the length and number of rest breaks , where the longer breaks and more breaks then the value of ART will be smaller .